2020
DOI: 10.3390/biology9120420
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungi as Potential Biological Control Agents against Grapevine Trunk Diseases in Alentejo Region

Abstract: Grapevine trunk diseases (GTDs) are the most widespread fungal diseases, affecting grapevines in all the major growing regions of the world, and their complete eradication is still not possible. Aiming to search alternatives to avoid the spread and high incidence of these diseases, the present work intended to molecularly identify the grapevine endophytic community, the phytopathogenic fungi associated with GTDs in vineyards within the Alentejo region, and to test potential antagonist microorganisms as biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…For example, endophytic fungi, isolated from Pelargonium graveolens, Melia azedarach, Chenopodium album, and Malva parviflora, are rich sources of secondary metabolites for use in bio-control [13]. Almeida et al found that endophytes were promising biological control agents because of their antagonistic activity toward the mycelial growth of grapevine trunk diseases (GTD)-associated fungi [16]. Some endophytic fungi can also promote plant growth by increasing plant access to nutrients (nitrogen, phosphorus, potassium, zinc, and iron), producing phytohormones, and increasing plant stress tolerance [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, endophytic fungi, isolated from Pelargonium graveolens, Melia azedarach, Chenopodium album, and Malva parviflora, are rich sources of secondary metabolites for use in bio-control [13]. Almeida et al found that endophytes were promising biological control agents because of their antagonistic activity toward the mycelial growth of grapevine trunk diseases (GTD)-associated fungi [16]. Some endophytic fungi can also promote plant growth by increasing plant access to nutrients (nitrogen, phosphorus, potassium, zinc, and iron), producing phytohormones, and increasing plant stress tolerance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have pointed to an interest in endophytic fungi as putative BCAs against GTD pathogens [ 89 , 90 ], but, unfortunately, there have not yet been any trials in plants to test their effectiveness. One of the most promising fungal BCAs against GTDs is the oomycete Pythium oligandrum , which is a frequent inhabitant of the grapevine root system from which different isolates have been obtained [ 80 , 91 ].…”
Section: The Grapevine Microbiome As a Source Of More Efficient And P...mentioning
confidence: 99%
“…It is common as an endophyte or pathogen of vascular plants in both temperate and tropical regions ( 3 , 4 ). It infects stems ( Vitis [ 5 , 6 ], Vaccinium [ 7 ]), leaves ( Rosa [ 8 ], Parthenocissus [ 3 ], Populus [ 9 ]), fruits ( Malus [ 10 ], Olea [ 11 ]), and roots ( Vitis [ 12 ]) and is also a candidate for biological control of plant diseases ( 9 , 12 ). In addition to plants, this fungus was also isolated from marine sponges ( 13 ), humans ( 4 ), and as a pathogen from insects ( 14 ).…”
Section: Announcementmentioning
confidence: 99%